Towards efficient conversion of sucrose to 1,2-propanediol selectively over Cu-La on activated carbon support - Anilan, Anusree Elavanaparambil; Sreekantan, Sreejith; Racha, Arundhathi; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2025)
In this study, we investigated the conversion of sucrose to 1,2-propanediol (1,2-PDO) using various Cu-La metals supported on activated carbon (AC), a versatile support known for its hydrophobicity and high surface area. Among the catalysts tested, 6% Cu-20% La/AC demonstrated the highest activity, achieving a 72% yield of 1,2-PDO under optimal reaction conditions of 200 degrees C, 40 bar H2, and 6-h reaction time. Comparative studies using cellulose, sucrose, glucose, and fructose as substrates identified sucrose as the most favorable feedstock for 1,2-PDO production. Detailed catalyst characterization (XRD, TEM, FE-SEM, TPR, TPD, XPS) revealed that the high dispersion, presence of metallic copper, and synergy between Cu and La, along with the presence of optimal acidic and basic sites, were responsible for the catalyst's high selectivity of 1,2-PDO. Additionally, the effect of different supports, including HY, NaY, HZSM-5, NaZSM-5, gamma-Al2O3, and AC, on sucrose conversion was examined, with AC showing superior performance. The catalyst's reusability was also assessed.Graphical abstractInvestigation of Cu-La metals supported on activated carbon for the catalytic conversion of sucrose to 1,2-propanediol, with an emphasis on choice of support, feedstock selection, catalyst performance, and stability under optimized reaction conditions.
Keywords: 1; 2-Propanediol; Biomass conversion; Biomass-to-chemicals; Hydrogenation